Vendetta w rodzinie albańskiej a prawa dziecka - Tuci, Alfred (Pedagogika Społeczna Nova, 2026)
The article addresses the issue of vendetta in the traditional Albanian family in the context of children’s rights and contemporary standards of human rights protection. The analysis is based on the norms of Albanian customary law – the Kanun of Lekë Dukagjini, which for centuries has regulated family life, clan relations, and the principles of honor, hospitality, and blood feud. Particular attention is paid to the impact of the Kanun on the situation of the child, whose subjectivity and safety are often subordinated to the interests of the clan and the obligation to preserve honor. Vendetta, understood as a social and moral duty, leads to the isolation of children, restrictions on their freedom, their right to education, and their sense of security, and in extreme cases poses a direct threat to their lives. The article highlights the contradiction between traditional cultural norms and modern legal regulations, including the Constitution of the Republic of Albania and international instruments for the protection of children’s rights, especially the European Convention on Human Rights. It also emphasizes the role of non-governmental organizations, social mediators, and international initiatives (including UNICEF) in preventing violence and protecting children affected by vendetta. The article argues that despite ongoing social and legal transformations, the Kanun still significantly influences family life in northern Albania, making the protection of children’s rights a particularly urgent issue requiring comprehensive educational, legal, and institutional measures.